Implementasi Teknologi Tepat Guna untuk Peningkatan Kualitas Olahan Jamur pada Usaha Jamur Tiram - Dwi Sulistyaningsih; Achmad Solichan; R. Ery Wibowo Agung (Universitas Muhammadiyah Semarang, 2018)
Oyster mushroom farmer group REJOSARI MAKMUR and MANDIRI are two mushroom business groups in Meteseh village which was formed in response to the decline of the indigenous economy. They process mushrooms into chips sold in traditional markets. Their problems are low production capacity, low product diversification, oil content in chips is still high, and product packaging is not carried out properly. The objectives are (1) to develop business partners' mushroom so that they are able to become economically independent communities, (2) improve creative and innovative skills, use appropriate technology skills in draining, packaging, storage and product marketing skills. The method of achieving the goal is to increase production capacity through baglog enhancement, improve the skills and creativity of making various processed mushroom foods, applying oil slicing machines, and developing methods for packaging mushroom food products using packaging machines and labeling on product packaging. The results showed that the durability of chips for not sluggish and rancid increased from 4 days to 16 days. Mushroom entrepreneurs have been able to make various processed mushroom foods from 1 (chips) into several products including nuged and mushroom meatballs. Packaging becomes better, attractive and tight so that the flavor increases and food resistant.Keywords: Oyster mushroom, capacity, packaging, product diversification